2013
DOI: 10.1038/labinvest.2013.89
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of tumor necrosis factor (TNF) receptors in chronic intestinal inflammation: TNFR1 ablation boosts systemic inflammatory response

Abstract: Tumor necrosis factor-a (TNF-a) acts as a key factor for the development of inflammatory bowel diseases (IBDs), whose function is known to be mediated by TNF receptor 1 (TNFR1) or TNFR2. However, the precise role of the two receptors in IBD remains poorly understood. Herein, chronic colitis was established by oral administration of dextran sulfate sodium (DSS) in TNFR1 or TNFR2 À / À mice. Unexpectedly, TNFR1 or TNFR2 deficiency led to exacerbation of signs of colitis compared with wild-type (WT) counterparts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 40 publications
2
29
0
Order By: Relevance
“…TNFR2 signaling mediates the activation of MLCK and the change in localization of occludin. TNFR2 signaling also induces infiltration of macrophages and neutrophils into the lamina propria and activates Th17 cells (50,51). Su et al (20) reported that the induced expression of TNFR2 in murine colitis promoted apoptosis of intestinal epithelial cells, chemokine overexpression, and exacerbation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…TNFR2 signaling mediates the activation of MLCK and the change in localization of occludin. TNFR2 signaling also induces infiltration of macrophages and neutrophils into the lamina propria and activates Th17 cells (50,51). Su et al (20) reported that the induced expression of TNFR2 in murine colitis promoted apoptosis of intestinal epithelial cells, chemokine overexpression, and exacerbation of inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…While some of the epidemiological studies did observe sexually dimorphic effects, other studies did not [72]. Interestingly however, several of the identified sexually dimorphic genes containing a function in inflammatory processes have previously been linked to IBD including Ccr3 [73], Ccl11 [74], Ncf1 [75] and Tnfr [76]. Apart from genes playing a role in immune response and inflammation, we identified cancer-relevant genes in the colon showing sex-differential expression using IPA.…”
Section: Discussionmentioning
confidence: 99%
“…A study using a colitis mouse model suggests that both TNFR1 and TNFR2 have protective functions in intestinal inflammation[31]. Herein, intestinal inflammation was provoked by oral application of dextran sulfate in mice deficient for TNFR1 or TNFR2 as well as wildtype controls.…”
Section: Tnf Biology and Its Signaling Pathwaymentioning
confidence: 99%
“…Herein, intestinal inflammation was provoked by oral application of dextran sulfate in mice deficient for TNFR1 or TNFR2 as well as wildtype controls. TNFR1 or TNFR2 ablation resulted in exacerbation of colitis, possibly due to increased apoptosis of colonic epithelial cells[31]. However, in other studies a central role of TNFR2 in mucosal inflammation has been proposed.…”
Section: Tnf Biology and Its Signaling Pathwaymentioning
confidence: 99%